Evaluation of hepatocellular dysfunction and its association with severity in dengue patients - K. T., Chandrasekar; Dutta, Tarun Kumar; R., Arun Kumar; S., Lokesh; Charles, M. V. Pravin (International Journal of Advances in Medicine, 2019)
Background: Dengue is a mosquito-borne infection that in recent years has become an important disease of international public health concern. Dengue virus infections and illness when symptomatic, that patients tend to present with a significantly wide variety manifestations. The aim of the study was to evaluate liver dysfunction in patients with dengue infections. Methods: The present study was undertaken as an observational cross-sectional study the period June 2017 to December 2018. The details of all patients with serologically proved dengue fever admitted in the hospital were reviewed. Data including routine blood count, liver function test (LFT), prothrombin time (PT), activated partial prothrombin time (APTT), abdominal ultrasonography was studied. Statistical analysis: Data was analyzed using SPSS version 21.0. Difference between proportions was tested by using chi square test. Pearson correlation coefficient was used to measure linear correlation between two continuous variables. A p value <0.05 was considered statistically significant. Results: Majority of the study participants were in the age group of 16-30 years (57.5%) and were males (64.5%). Fever, Headache and joint pain were the most common symptoms noted among the study participants. Majority of the study participants were found to have elevated levels of SGOT (75.3%), SGPT (64.2%) levels and lower levels of serum albumin (68.6%) on evaluation. Statistically significant association was observed between elevated liver enzymes and presence of features of dengue haemorrhagic fever. Conclusions: Considerably high proportion of patients with dengue infection were found to have hepatic dysfunction in the form of deranged liver enzymes.